EFFECT ASTANGA YOGA PRACTICES ON SELECTED PHYSICAL AND PSYCHOLOGICAL VARIABLES AMONG OBESE MEN ADVOCATES (International Journal of Food and Nutritional Sciences, 2022)
Background: Obesity is a growing global health concern, affecting individuals of all ages and genders. Physical inactivity and psychological stress are prominent factors contributing to obesity. Astanga Yoga, a traditional form of yoga that integrates physical postures, breath control, and meditation, has gained popularity as a holistic approach to improve both physical and mental well-being. This study aims to investigate the effects of Astanga Yoga practices on selected physical and psychological variables among obese men advocates.